2006
DOI: 10.1021/jp0644006
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Photoemission for Probing Charging/Discharging Dynamics

Abstract: A novel technique is introduced for probing charging/discharging dynamics of dielectric materials in which X-ray photoemission data is recorded while the sample rod is subjected to (10.0 V square-wave pulses with varying frequencies in the range of 10 -3 to 10 3 Hz. For a clean silicon sample, the Si2p(Si 0 ) peak appears at correspondingly -10.0 eV and +10.0 eV binding energy positions (20.0 eV difference) with no frequency dependence. However, the corresponding peak of the oxide (Si 4+ ) appears with less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…2, we display C1s, Si2p and Rb3d peaks recorded at 0.01 Hz, where each peak exhibits a slightly different shift due the different extent of charging they experience. This is similar to our previous observations with other composite samples [33][34][35]. Whereas, the Si2p peak separation is exactly the same as that of O1s (18.2 eV), the Rb3d and C1s peaks are separated by 18.1 and 18.0 eV, respectively, revealing that to some extent, the Rb and C moieties are electrically isolated (and chemically distinct) from each other.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…2, we display C1s, Si2p and Rb3d peaks recorded at 0.01 Hz, where each peak exhibits a slightly different shift due the different extent of charging they experience. This is similar to our previous observations with other composite samples [33][34][35]. Whereas, the Si2p peak separation is exactly the same as that of O1s (18.2 eV), the Rb3d and C1s peaks are separated by 18.1 and 18.0 eV, respectively, revealing that to some extent, the Rb and C moieties are electrically isolated (and chemically distinct) from each other.…”
supporting
confidence: 91%
“…Using a slightly different strategy and by applying voltage stress to the sample while recording XPS spectra, we have shown that the extent of charging can be controlled, as a result of which a range of analytical and electrical information can be extracted [26][27][28][29][30][31]. In addition to static information derived from application of d.c. voltage stress, dynamical information can also be extracted by application of the voltage stimuli in the form of square wave pulses, as we have recently reported [29,[32][33][34][35]. In our previous measurements we used an unmonochromatized X-ray source where, in addition to characteristic Mg Ka radiation, it also emits wide bremstrahlung radiation and low energy electrons, which are known to affect charging of the samples under investigation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In conventional data gathering mode the sample is grounded, and the position as well as the intensity of the peaks are recorded in a static fashion [20]. Although several reports have appeared in the literature related to dynamical XPS measurements in the two extreme ends, very fast (nanoseconds to attoseconds) [21][22][23][24], and very slow (minutes to hours) [25][26][27] through various publications, the basic principles and techniques for implementing such measurements employing very simple modification to conventional instruments [28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…X-Ray Photoelectron Spectroscopy (XPS) was used to investigate surface photovoltaic and photoconductivity effects in nanocomposite surfaces without using femtosecond or picoseconds light or X-ray pulses. [14][15][16][17][18] Here, we extend such use of XPS to investigate HEE in plasmonic MIM structures. Laser excitation is used to illuminate the plasmonic surfaces (Figure 1(a)).…”
mentioning
confidence: 99%